Mast cell tumor in dogs : incidence and histopathological characterization - Grabarević, Željko (Array, 2009)
Abstract: Incidence of mast cell tumors, their distribution according to sex, breed, age and localisation in Croatia is not established yet. Also, the statistical significance of the various histopathological parameters according to Patnaik’s scheme, in the diagnostics of the tumor grade was not performed. Investigation analysed mast cell tumors histopathologicaly characterized at the Department of General Pathology and Pathological Morphology of the Veterinary Faculty Zagreb from January 1st 2002 to Dezember 31st 2006. Sex, age, breed, localisation and tumor grade of each animal with tumor was recorded and statisticaly evaluated. Each histopathological variable was scored and compared with tumor grade. In the analyzed period, totally 1630 tumors were recorded, and mast cell tumors were found in 106 animals or in 6.5% of all cases. With statistically significant difference, this tumor was found in more cases in male dogs, and average age was 6.96 years. Boxers and retrievers were most frequent breeds, and localization was mostly on legs. Grade I tumor was found in 15.09%, grade II in 44.34% and grade III in 28.3% of animals. There were no significant correlations between tumor grade and age, breed, sex or localization. Considering the lesion scores compared with grade, statistically significant differences were found in cell shape, number of nucleoli, anisocytosis, anisokariosis, karyomegaly, mitoses, necroses, hemorrhages, cellularity, cell borders and collagenolysis